Efficiency Analysis of eNodeB Base Station and 4G LTE Quality of Service: A Case Study in Vientiane Capital - Khothpanya, Ngonkham; Thongphanh, Phutsavanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
Currently, the growth of mobile data usage in high-density urban areas often leads to degraded signal quality and increased interference due to network congestion, directly impacting overall Service Performance. Therefore, this research aims to analyze the efficiency of the eNodeB base station system and evaluate the Quality of Service (QoS) of Lao Telecommunications’ 4G LTE network in the Vientiane Capital area. The methodology focuses on analyzing the hardware architecture of the Huawei DBS3900 series and conducting empirical field testing across four strategic locations: the Mekong Riverside area, Sihom area, Pha That Luang area, and Talat Sao building. The diagnostic tools utilized for measurement include mobile network testing software to record key technical parameters, such as Reference Signal Received Power (RSRP), Signal to Interference plus Noise Ratio (SINR), and data transmission speed (Throughput). The results indicate that: 1. Regarding hardware architecture: The Huawei DBS3900 series eNodeB features a distributed architecture separating the BBU and RRU modules, providing high stability and robust capacity to support high-speed data transmission benchmarks. 2. Regarding technical parameters: The RSRP signal strength in all tested areas remains within a favorable range, with average values between -70.00 dBm and -85.00 dBm. However, in high-density areas like Pha That Luang and Talat Sao, the SINR values exhibit noticeable fluctuations caused by co-channel and adjacent-channel interference. The average download throughput ranges from 26.4 Mbps to 29.3 Mbps, while the average upload throughput reaches 30.8 Mbps, satisfying standard service benchmarks. 3. Regarding physical optimization: The findings demonstrate that physical parameter optimization, specifically antenna tilting adjustments (both mechanical and electrical), plays a critical role in mitigating signal interference and enhancing network QoS in dense urban environments.